Pengaruh Penambahan Serat Kapas (Gossypium sp) Terhadap Kekuatan Tarik Diametral Resin Komposit Flowable - Azizy, Aliega Fahmi Noor; , drg. Dendy Maryanto, MDSc (2017)
Background:Flowable composite resin is one of composite resin type that has a low viscosity. This composite resin has a small filler load in result low on its mechanical strength. The addition of fiber can improve the mechanical strength of flowable composite resin. Utilization of natural fiberget more enthused for its environmentally friendly and inexpensive. One of the natural fiber is Cotton fiber (Gossypium sp) fiber containing cellulose as a reinforcement of its mechanical strength. Objective: To determine the effect of adding Cotton fiber to diametral tensile strength andflowable composite resins. Methods: This study use post-test-only control group design which measures diametral tensile strength of flowable composite resin without the addition of Cotton fibers and with the addition of a Cotton fibers. The object of research is divided into 2 groups: control group and the treatment group in 32 samples. Results: The results from Independent t-test showed that there were significant mean difference (<0.05) between the treatment group (43,40057MPa) and the control group (38,50407MPa). Conclusions: The addition of Cotton fiber influencediametral tensile strength flowable composite resin.The addition of Cotton fiber improving the diametral tensile strength flowable composite resin. Keywords: flowable composite resin, diametral tensile Strength, cotton fiber (Gossypium sp).